Pulp revascularization: an alternative treatment to the apexification of immature teeth - Albuquerque, Maria Tereza Pedrosa [UNESP]; Nagata, Juliana Yuri; Soares, Adriana De Jesus; Zaia, Alexandre Augusto (Faculdade São Leopoldo Mandic, 2014)
Pulp revascularization can be considered as a current alternative treatment to apexification, recommended for immature teeth cases, requiring endodontic treatment. Apexification involves long-term periodic exchanges of a calcium hydroxide paste into the root canal to induce the formation of a calcified barrier. Despite being the most classically therapy employed for these cases, the permanence of calcium hydroxide for long periods of time and also the successive changes may lead to a weakening of the root due to its hygroscopic properties and the proteolytic activities of calcium hydroxide, increasing the risk of fractures and contamination of the pulp space. Thus, a constant search for new treatment alternatives that provide the end of root development have been done to avoid the risk of future root fractures. So, revascularization has emerged as a new treatment option for cases of undeveloped teeth, that provides not only apical closure, as apexification, but also increase the dentin walls thickness. In the literature, there is an assortment of treatment protocols employing pulp revascularization procedure in attempt to attain the best way to achieve success. Assuming the diversity of protocols for revascularization treatment, it is important to go deep in the literature to collect, describe and discuss these protocols guiding new researches in this field and also conducting the clinicians. Therefore, this review aims to assess the literature on the different revascularization protocols.

A revascularização pulpar pode ser considerada atualmente como um tratamento alternativo à apicificação e é indicado para dentes com rizogênese incompleta e necessidade de tratamento endodôntico. A apicificação envolve a realização de trocas periódicas em longo prazo de uma pasta de hidróxido de cálcio com o objetivo de formar uma barreira calcificada. Apesar de ser a terapia mais empregada, a permanência desta medicação por longos períodos e as trocas sucessivas, podem levar à fragilização da raiz devido às propriedades higroscópicas e proteolíticas do hidróxido de cálcio, aumentando o risco de fraturas e contaminação do espaço pulpar. Desta forma, tem-se buscado novas alternativas de tratamento que possibilitem o fechamento do forame apical dos dentes imaturos sem que ocorra a fragilização dos mesmos. A revascularização pulpar tem surgido como uma nova opção de tratamento para estimular o término do desenvolvimento radicular e não apenas o fechamento apical. Há na literatura uma variedade de protocolos utilizando esta técnica, buscando sempre alcançar o sucesso no tratamento. Diante dessa variedade, é de grande importância a realização de uma revisão de literatura sobre revascularização pulpar visando reunir, descrever e discutir os diferentes protocolos, para que possam direcionar novas pesquisas e ser empregada de forma adequada pelo clínico. O objetivo desse trabalho é revisar na literatura os diferentes protocolos de revascularização pulpar.
Revascularização pulpar: tratamento alternativo à apicificação de dentes jovens com rizogênese incompleta
Keywords: Dental pulp; Endodontics; Regeneration; Polpa dentária; Endodontia; Regeneração